A pedagogia psicodramática na educação do filosofar: humanização, inovação e tecnologia. - Martins, José Lucas (2023)
This research emerges from the formative experiences of the researcher. Driven by the educational focus of psychodrama, part of Jacob Levy Moreno's socionomic science, the author delved into the psychodramatic pedagogy of Maria Alicia Romaña. While teaching philosophy in a public school in Santa Catarina, the challenge of engaging students sparked an interest in applying the psychodramatic pedagogy method, enabling real, symbolic, and imaginary representations that amplified the understanding of philosophical concepts. To further study this method, the researcher enrolled in the Professional Master's in Education and New Technologies at the International University Center – UNINTER. The scope of the research focuses on exploring the relationship between psychodramatic pedagogy and contemporary educational technologies with the education of philosophizing, aiming to provide an enriching experience for educators in the field and students. The general objective of the research was to develop a comprehensive virtual action plan that guides the application of psychodramatic pedagogy in the journey of philosophizing education in High School. Specific objectives were outlined, including exploring Moreno's socionomic science, a thorough investigation of Romaña's psychodramatic pedagogy, drawing a historical overview of philosophizing education in Brazil, and disseminating the product among teachers. The study is classified as strategic basic research, adopting a qualitative and exploratory approach. The integrative literature review outlined the pre-existing approaches, identified gaps in knowledge, and provided the presentation of an active proposal to enrich the education of philosophizing, harmonizing it with contemporary demands. The production of the virtual action plan embraces the use of various digital tools, providing an adaptable and dynamic resource, enriching the learning experience for both educators and students. The outlined results indicate gains for the education of philosophizing with the application of psychodramatic pedagogy and contemporary educational technologies, providing an innovative educational intervention and an engaging and humanized learning experience in the context of High School.